Melanocortin 4 receptor activation inhibits presynaptic N‐type calcium channels in amygdaloid complex neurons. (18th June 2014) - Agosti, Francina; López Soto, Eduardo J.; Cabral, Agustina; Castrogiovanni, Daniel; Schioth, Helgi B.; Perelló, Mario; Raingo, Jesica
Abstract The melanocortin 4 receptor (MC4R) is a G protein‐coupled receptor involved in food intake and energy expenditure regulation. MC4R activation modifies neuronal activity but the molecular mechanisms by which this regulation occurs remain unclear. Here, we tested the hypothesis that MC4R activation regulates the activity of voltage‐gated calcium channels and, as a consequence, synaptic activity. We also tested whether the proposed effect occurs in the amygdala, a brain area known to mediate the anorexigenic actions of MC4R signaling. Using the patch‐clamp technique, we found that the activation of MC4R with its agonist melanotan II specifically inhibited 34.5 ± 1.5% of N‐type calcium currents in transiently transfected HEK293 cells. This inhibition was concentration‐dependent, voltage‐independent and occluded by the Gαs pathway inhibitor cholera toxin. Moreover, we found that melanotan II specifically inhibited 25.9 ± 2.0% of native N‐type calcium currents and 55.4 ± 14.4% of evoked inhibitory postsynaptic currents in mouse cultured amygdala neurons. In vivo, we found that the MC4R agonist RO27‐3225 increased the marker of cellular activity c‐Fos in several components of the amygdala, whereas the N‐type channel blocker ω conotoxin GVIA increased c‐Fos expression exclusively in the central subdivision of the amygdala. Thus, MC4R specifically inhibited the presynaptic N‐type channel subtype, and this inhibition may be important for the effects of melanocortin in the central subdivision of the amygdala.